Identificação de enfermeiras com o trabalho e com o hospital: o olhar de diferentes gerações - Daniela Soares Santos (2011)
In the public organizations, due to job security and increased life expectancy of the population, it deserves to point out the contribution of different generations, which bring knowledge and the specific characteristics of the historical moments when they lived, which relate, also, in a different way to organization and work. The aim of this study is to analyze the identification of nurses from different generations with theorganization and work in a public hospital in Belo Horizonte. A descriptive analytical case study was developed, with qualitative features, in which the subjects were composed of 13 nurses from different generations, of the staff of the Municipal Hospital Odilon Behrens. The definition of the subjects was based on the characteristics of a profession dominated by women and most representative in the hospital sector, as well as the range of contributions and complementarity of knowledge from different generations of nurses. Data collection consisted of nurses headcount in the hospital, per generation, and then of scheduling and conducting semi-structured interviews until achieving saturation of the data. Data analysis was performed using content analysis. In summary, the results showed that nurses recognized good inter-professional and interpersonal relationships at work, but, in some cases, there are conflicts between co-workers and superiors. The representatives of the Baby Boom generation have less knowledge of new technologies and believe that younger workers have less involvement with the hospital. The nurses of Generations X and Y dominate the technology and, although they recognize the experience of Baby Boomers, they believe that they are resistant to change and organizational innovations. In general, nurses are identified with the hospital and the work, mainly in the employment related actions, but they recognize the deficiencies of the organization. There are differences in the way and the intensity with which the identification occurs in the three generations, but it was possible to identify convergences of opinion among the Baby Boomers, X and Y nurses, on issues such as remuneration, professional development, working conditions, responsibilities and workload